Перевидання “Українських народних мелодій” К. Квітки: наукове значення і проблематика - Іваницький, А. (Народна творчість та етнографія, 2005)
The author of the article who has prepared the given anthology for republishing explains several important critical-textological principles of the methodology. Alongside with the collection never published Kvitka's "Commentary" is ready to be issued. The article speaks on the uniqueness of field and theoretical work done by a great ethnomusicologist Klyment Kvitka. The author presents the goal of the present edition of the anthology, which is to edit, to remove mistakes of the previous edition and to make a critical-textological analysis of the work. He illustrates Kvitka's specific features and approaches of ethnomusicological work as well.